TET enzymes in neurophysiology and brain function - Antunes, Cláudia (2019)
The dynamic nature of epigenetic DNA modifications is crucial for regulating gene expression in an experience-dependent manner and, thus, a potential mediator of neuronal plasticity and behavior. The discovery of the involvement of 5-hydroxymethylcytosine (5hmC) and Ten Eleven Translocation (TET) family of enzymes in the demethylation pathway uncovered a potential link between neuronal TET protein function and cognitive processes. In this review, we provide an overview on how profile of 5hmC and TET enzymes are powerful mechanisms to explain neuronal plasticity and long-term behaviors, such as cognition. More specifically, we discuss how the current knowledge integrates the function of each TET enzyme in neurophysiology and brain function.